A new species of Biribellus Galileo, 1987 (Coleoptera, Cerambycidae, Prioninae, Anacolini) from Peru and key to species - Santos-Silva, Antonio; Hernandez, Juan José Ramírez; Galileo, Maria Helena M. (Zootaxa, 2018)
Biribellus isabelae, a new species from Peru, is described and illustrated. The new species is compared with B. huedepohli (Galileo, 1987), a species with a very similar general appearance. An updated key to species of Biribellus is provided.